2014
DOI: 10.7567/jjap.53.071301
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of slicing-induced damage in hexagonal SiC by wire sawing with loose abrasive, wire sawing with fixed abrasive, and electric discharge machining

Abstract: Crystal damage induced in hexagonal SiC by cutting was characterized by transmission electron microscopy and Raman scattering. Wiresawing with loose abrasive (WSLA) induces stacking faults (SFs), dispersive triangular crystal disordered areas, and dislocation half-loop bundles. Wiresawing with fixed abrasive (WSFA) induces SFs, crystal disordered layers, and dislocation half-loop bundles. Electric discharge machining (EDM) predominantly forms silicon, carbon, and 3C-SiC by 6H-SiC decomposition. The mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…399,400) It is also essential to remove the subsurface damage introduced during a polishing process by either chemical-mechanical polishing or appropriate H 2 etching, 401) since the mechanical stress induced by surface polishing can create BPD half loops near the surface. [402][403][404] If such BPD half loops remain at the time of epitaxial growth, the BPD (and TED) density in the epitaxial layer will increase. Using the latest growth technology, the BPD-TED conversion ratio exceeds 99.98% and the BPD density in SiC epitaxial layers is about 0.01-0.2 cm −2 .…”
Section: Threshold Condition For 1ssf Expansionmentioning
confidence: 99%
“…399,400) It is also essential to remove the subsurface damage introduced during a polishing process by either chemical-mechanical polishing or appropriate H 2 etching, 401) since the mechanical stress induced by surface polishing can create BPD half loops near the surface. [402][403][404] If such BPD half loops remain at the time of epitaxial growth, the BPD (and TED) density in the epitaxial layer will increase. Using the latest growth technology, the BPD-TED conversion ratio exceeds 99.98% and the BPD density in SiC epitaxial layers is about 0.01-0.2 cm −2 .…”
Section: Threshold Condition For 1ssf Expansionmentioning
confidence: 99%
“…Ishikawa et al reported that basalplane dislocation loops and stacking faults are introduced in the subsurface by the slicing process, and also that some such defects may remain after the buffing process. 29) Figures 3(a) and 3(b) show CDIC images before and after the CMP process. No significant defects or scratches are detected on the wafer surface.…”
Section: Resultsmentioning
confidence: 99%
“…Surface and subsurface damage has been widely investigated in the machining of SiC materials, as it is directly related to the surface integrity, particularly for EDM. Melting and evaporating the workpiece material allows EDM to be employed for drilling [12], milling [13,14], cutting [15], and slicing [16] of SiC irrespective of its hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal energy was suggested to be a main material removal mechanisms in EDM of SiC, and it causes surface damages such as cracks, pores, and rectangular pits [15]. EDM predominantly decomposed SiC and formed Si, C, and cracks [16]. An extra layer over the top of the original surface and a porous layer with plenty of voids underneath was formed through EDM of RB-SiC [10].…”
Section: Introductionmentioning
confidence: 99%